The outcome of conventional open reduction approach vs endoscopic approach for orbital floor repair - Ravi Katrolia; Shadab Mohammad; Divya Mehrotra; Geeta Singh; Deepika Jain; Ezhilarasi; M Haaris Khan; M.V. Sowmya (Journal of Oral Biology and Craniofacial Research)
Introduction: Blunt trauma to the orbital rim is a frequent cause of both orbital fractures and damage to the surrounding facial bones and soft tissues. The inception of endoscopy and minimal invasive intervention has revolutionized the surgical treatment of blow out fracture of orbital walls. Thus, the present study was conducted to compare the outcome of conventional open reduction approach with endoscopic approach for orbital floor repair. Materials and method: The study included 10 patients with clinical and radiographic evidence of orbital floor fracture, divided randomly into two groups: Group I-operated using endoscopic approach; and Group II- operated using conventional external approach. All the patients were evaluated clinically preoperatively, immediate post-operative and after 1 month for Diplopia, Extrinsic ocular motility, Enophthalmos and Hypoglobus. Results: The study consisted of 40% females and 60% males, with mean age of Endoscopic and Conventional group being 27.20 ± 6.14 years and 27.60 ± 7.23 years respectively. In relation to diplopia, an insignificant difference was observed statistically. The mean change in enophthalmos and hypoglobus in endoscopic and conventional group showed a significant difference statistically (p < 0.001). Unrestricted ocular motility was present only in one case of each group and significantly increased to 5 cases in both the groups (p = 0.048). The mean duration of surgery in endoscopic and conventional group showed a significant difference statistically. Conclusion: Diplopia, hypoglobus and Enophthalmos correction was better achieved in endoscopic group as compared to conventional group. But duration of surgery was more in endoscopic group as compared to conventional group.